Saraswati with eight hands - 027 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ The lute, though broken, suggests that the deity here is Saraswati. Other typical attributes of Saraswati here are : the bottom left hand, though partly broken has a scroll. There is the Japamala (the prayer beads) in one of the hands.